The persistent shadow of disparity across the Atlantic: child health determinants and policy implications in Europe and North America - Antonio D’Avino; Angel Carrasco-Sanz; Anna Libera Latino; Maria Pastore; Ida Giardino; Massimo Pettoello-Mantovani; Francesca Scaltrito; Domenico Adduce; Maria Teresa Grimaldi; Luigi Nigri (Global Pediatrics)
Child health serves as a critical barometer of a society's well-being, yet profound disparities persist globally, stemming from ''unequal beginnings'' rooted in socioeconomic, environmental, and systemic factors. This brief review examines the complex determinants of child health inequities across Europe and draws comparisons with the United States. In Europe, despite historical health gains, stagnation and widening gaps are observed in child mortality, chronic illnesses, and mental health, exacerbated by poverty, educational disparities, and fragmented healthcare systems. A significant barrier to effective policy is the pervasive lack of consistent and comparable child health data. In the United States, similar socioeconomic disparities are compounded by deep-seated racial inequities in healthcare access and quality, highlighting the pervasive influence of structural factors beyond insurance coverage. Emerging challenges, such as the escalating burden of mental health conditions, lifestyle-related diseases, and the disproportionate impact of climate change through ''systemic cooling poverty,'' present new complexities. Artificial intelligence offers transformative potential for pediatric care but also carries risks of exacerbating existing disparities if not ethically and equitably implemented. Addressing these multifaceted challenges necessitates a concerted, multi-sectoral approach, emphasizing child-centric integrated care, robust data systems, and sustained political commitment to dismantle the systemic roots of inequity.